2022
DOI: 10.3390/nu14142824
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Supplementation in Cancer Cachexia: Mechanisms and a Review of the Pre-Clinical Literature

Abstract: Cancer cachexia (CC) is a complex syndrome of bodily wasting and progressive functional decline. Unlike starvation, cachexia cannot be reversed by increased energy intake alone. Nonetheless, targeted nutritional support is a necessary component in multimodal syndrome management. Due to the highly catabolic nature of cancer cachexia, amino acid supplementation has been proposed. Interestingly, leucine has been found to increase protein synthesis and decrease protein degradation via mTORC1 pathway activation. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 147 publications
0
30
0
Order By: Relevance
“…Positive effects of Leu supplementation were observed in animals fed with a high fat diet, with attenuation of mitochondrial dysfunction, fat mass, and hyperglycemia [ 105 ]. A few studies performed in animal models of cancer cachexia have shown that a diet rich in Leu was able to stimulate, in a dose-dependent manner, protein synthesis in skeletal muscle, resulting in reduced loss of lean body mass and muscle wasting [ 111 ]. These data were supported by improvements in muscle strength, physical performance, and inflammatory status [ 111 ].…”
Section: Amino Acid Supplementation As Anticancer Therapy: Targeting ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Positive effects of Leu supplementation were observed in animals fed with a high fat diet, with attenuation of mitochondrial dysfunction, fat mass, and hyperglycemia [ 105 ]. A few studies performed in animal models of cancer cachexia have shown that a diet rich in Leu was able to stimulate, in a dose-dependent manner, protein synthesis in skeletal muscle, resulting in reduced loss of lean body mass and muscle wasting [ 111 ]. These data were supported by improvements in muscle strength, physical performance, and inflammatory status [ 111 ].…”
Section: Amino Acid Supplementation As Anticancer Therapy: Targeting ...mentioning
confidence: 99%
“…A few studies performed in animal models of cancer cachexia have shown that a diet rich in Leu was able to stimulate, in a dose-dependent manner, protein synthesis in skeletal muscle, resulting in reduced loss of lean body mass and muscle wasting [ 111 ]. These data were supported by improvements in muscle strength, physical performance, and inflammatory status [ 111 ]. Simultaneously, skeletal muscle mitochondrial biogenesis was ameliorated after Leu supplementation in tumor-bearing rats, together with the increased expression of markers related to oxidative phosphorylation and energy production [ 111 ].…”
Section: Amino Acid Supplementation As Anticancer Therapy: Targeting ...mentioning
confidence: 99%
See 1 more Smart Citation
“…That , Ras/Erk Signaling (which activated by S6K function) are Essential for Activating Protein Synthesis by Gq Protein-Coupled Receptor [123].…”
Section: The Role Of S6k In Cells Growth and In Nrf2 Synthesismentioning
confidence: 99%
“…The identification of the first signs of cachexia through non-invasive, simple methods can bring advantages in the management of this disease, with the possibility of intervening in the underlying disease. If cachexia is in the advanced phase, none of the diet-therapeutic interventions seem to reach the desired goal [ 28 , 29 , 30 ]. This study aims to clarify the correlation between BIA-measured parameters, clinical parameters, and other nutrition-related assessments.…”
Section: Introductionmentioning
confidence: 99%